Sequenceserver: A Modern Graphical User Interface for Custom BLAST Databases. (14th August 2019) - Priyam, Anurag; Woodcroft, Ben J; Rai, Vivek; Moghul, Ismail; Munagala, Alekhya; Ter, Filip; Chowdhary, Hiten; Pieniak, Iwo; Maynard, Lawrence J; Gibbins, Mark Anthony; Moon, HongKee; Davis-Richardson, Austin; et al.
Abstract: Comparing newly obtained and previously known nucleotide and amino-acid sequences underpins modern biological research. BLAST is a well-established tool for such comparisons but is challenging to use on new data sets. We combined a user-centric design philosophy with sustainable software development approaches to create Sequenceserver, a tool for running BLAST and visually inspecting BLAST results for biological interpretation. Sequenceserver uses simple algorithms to prevent potential analysis errors and provides flexible text-based and visual outputs to support researcher productivity. Our software can be rapidly installed for use by individuals or on shared servers.